Walnut peptide alleviates obesity, inflammation and dyslipidemia in mice fed a high-fat diet by modulating the intestinal flora and metabolites - Li, Lei; Wang, Si; Zhang, Tong; Lv, Bijun; Jin, Yanling; Wang, Yue; Chen, Xiaojiao; Li, Ning; Han, Niping; Wu, Yueying; Yuan, Jiali (Frontiers in Immunology, 2023)
Background: Obesity is a chronic disease in which the body stores excess energy in the form of fat, and intestinal bacterial metabolism and inflammatory host phenotypes influence the development of obesity. Walnut peptide (WP) is a small molecule biopeptide, and the mechanism of action of WP against metabolic disorders has not been fully elucidated. In this study, we explored the potential intervention mechanism of WP on high-fat diet (HFD)-induced obesity through bioinformatics combined with animal experiments.Methods: PPI networks of Amino acids and their metabolites in WP (AMWP) and "obesity" and "inflammation" diseases were searched and constructed by using the database, and their core targets were enriched and analyzed. Subsequently, Cytoscape software was used to construct the network diagram of the AMWP-core target-KEGG pathway and analyze the topological parameters. MOE2019.0102 was used to verify the molecular docking of core AMWP and core target. Subsequently, an obese Mice model induced by an HFD was established, and the effects of WP on obesity were verified by observing weight changes, glucose, and lipid metabolism levels, liver pathological changes, the size of adipocytes in groin adipose tissue, inflammatory infiltration of colon tissue, and intestinal microorganisms and their metabolites.The network pharmacology and molecular docking showed that glutathione oxide may be the main active component of AMWP, and its main targets may be EGFR, NOS3, MMP2, PLG, PTGS2, AR. Animal experiments showed that WP could reduce weight gain and improve glucose-lipid metabolism in HFDinduced obesity model mice, attenuate hepatic lesions reduce the size of adipocytes in inguinal adipose tissue, and reduce the inflammatory infiltration in colonic tissue. In addition, the abundance and diversity of intestinal flora were remodeled, reducing the F/B ratio, while theFrontiers in Immunology 2 intestinal mucosal barrier was repaired, altering the content of short-chain fatty acids (SCFAs), and alleviating intestinal inflammation in HFD-fed mice. These results suggest that WP intervenes in HFDinduced obesity and dyslipidemia by repairing the intestinal microenvironment, regulating flora metabolism and anti-inflammation.Conclusions: WP may be a potentially effective strategy for preventing and treating metabolic diseases and alleviating the intestinal flora disorders induced by them, providing experience for the development of WP.